(Im)Pertinences of a theoretical approach: the neoliberalization of nature - Buhler, Eve Anne; Gautreau, Pierre; Oliveira, Valter Lúcio (Sociedade & Natureza, 2020)
The increasing incorporation of biophysical processes into the market since the late 1980s, especially those related to agricultural frontiers, has been interpreted by some authors in terms of "neoliberalization of nature". Such a perspective has been quite fertile in critical studies of contemporary environmental issues, but it has been questionning by suffering serious objections. Some of these objections question the theoretical foundations of the neoliberalization of nature thesis and point to a certain conceptual lack in view of the diversity of definitions of the main concepts. Another type of objection refers to its low potential for empirical analysis, since it is so broad that it does not help to understand an inevitably incomplete and partial set of processes. The present contribution proposes a balance of the theoretical and empirical debates about the neoliberalization of nature, passing by its main authors and taking as reference some empirical researches that we have carried out about agribusiness in Brazil. We will discuss about how far its limits are due to inconsistencies pointed out by its critics or, instead (and beyond), to the lack of precautions in mobilizing an approach that deserves attention and interest nonetheless.